Autogenous Periosteal Graft Along with Open Flap Debridement Versus Open Flap Debridement Alone for the Treatment of Grade II Furcation Defect in Chronic Periodontitis Patients: A Systematic Review and Meta-Analysis - Swapna A. Mahale; Prasad Dhadse; Sumedha Thosar; Vedant Bhandari; Akhil Patil; Sadatullah Syed; Ranjeet Ajit Bapat; Tanay Chaubal; Sumaiya Zabin Eusufzai; Shahabe Saquib Abullais (Medicina)
Background and Objectives: Periodontal regeneration involves techniques intended at restoring the lost supporting tissue around a periodontally weakened tooth. These regenerative methods frequently utilize periosteal grafts to stimulate the evolvement of vital adjacent tissues. This paper intended to evaluate the use of autogenous periosteal grafts in treating grade II furcation defects (Glickman Classification 1953) in patients with chronic periodontitis. Materials and Methods: The databases MEDLINE (via PubMed), Cochrane, EBSCO, and Google Scholar were searched for papers published in English from January 1991 till December 2022. Three individuals examined the reclaimed articles according to the inclusion norms. Randomized controlled trials (RCTs) assessing the efficacy of autogenous periosteal grafts for treating Grade II furcation defects in chronic periodontitis patients were involved. Only four related studies were identified for data extraction, involving 80 patients aged 18 to 52 years. Outcome variables measured included horizontal bone loss (HD), vertical bone loss (VD), pocket depth (PD), clinical attachment level (CAL), bone height (BH), gingival recession (GR), plaque index (PI), and gingival index (GI). Data were examined using RevMan 5.4.1 software. Mean differences and 95% confidence intervals were employed to estimate effect sizes. Results: Both groups showed similar results for reductions in PI, GI, and BOP. However, The periosteal graft also yielded better outcomes for CAL gain, BH, and GR. The meta-analysis showed a significant overall effect of Periosteal Barrier Membrane (PBM) on horizontal and vertical bony change levels, but subgroup differences between unilateral and bilateral applications were not statistically significant due to high heterogeneity. Although the bilateral subgroup demonstrated significant benefits of PBM treatment, the overall findings across the clinical attachment level group remain inconclusive. Conclusion: Current evidence suggests that while PBM may benefit bilateral mandibular sites, and autogenous periosteal grafts offer no added advantage over OFD alone in Grade II furcation defects, the overall findings remain inconclusive.